This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The integrand looks dirty for being integrated , so let us try to simplify the integrand using the trigonometric tools.
s i n 2 ( x ) c o s 2 ( x ) 1 − c o s ( 2 x ) + 2 s i n 2 ( x ) c o s ( 2 x ) = sin 2 x cos 2 x 1 + cos ( 2 x ) ( 2 sin 2 x − 1 ) = sin 2 x cos 2 x 1 − cos 2 ( 2 x ) = sin 2 x cos 2 x sin 2 ( 2 x ) = 4 sin 2 x cos 2 x 4 s i n 2 ( 2 x ) = s i n 2 ( 2 x ) 4 s i n 2 ( 2 x ) = 4
Now we are astonished that the dirty integrand itself is a constant! Hence we have:
∫ 1 7 2 9 2 0 1 6 s i n 2 ( x ) c o s 2 ( x ) 1 − c o s ( 2 x ) + 2 s i n 2 ( x ) c o s ( 2 x ) d x = ∫ 1 7 2 9 2 0 1 6 4 d x
∫ 1 7 2 9 2 0 1 6 4 d x = 4 x ∣ ∣ ∣ ∣ 1 7 2 9 2 0 1 6 = 4 ( 2 0 1 6 ) − 4 ( 1 7 2 9 ) = 4 ( 2 0 1 6 − 1 7 2 9 ) = 4 × 2 8 7 = 1 1 4 8